Prevalence of smoking behaviour among adolescents in Ibadan south-east local government, Nigeria (2005)
The study investigated the prevalence of smoking among the adolescents in Ibadn south-east (local government,Nigeria). In all, 500(253 males and 247 females)adolescents were sampled. They were all senior secondary school students randomly selected from nineteen public senior secondary schools in Ibadan south east, Nigeria. Their ages ranged from 14-19 years (X̅=16.58; S. D=1.45). using both descritpive (frequency count and percentages) and inferential (Pearson correlation and chi-square at P<0.05) statistics it was observed that; more males than females indicated that they do smoke; smoking cuts across the ages sampled; adolescents from separated home tend to engage in smoking more tahn their colleagues from intact homes; and adolescents from homes whose parents were in the high soci-economi stratum tend to engage in smoking more than adolescents from homes whose parents were in the low socio-economic stratum. The study points to the fact that more aggressive counseling should be put in place in schools and married couples need to be counseled against divorce.